An investigation into the status of Thailand's music education systems and organisation. Issue 2 (23rd July 2021) - Laovanich, Vitchatalum; Chuppunnarat, Yootthana; Laovanich, Monsikarn; Saibunmi, Skowrung
Abstract: The purpose of this exploratory sequential mixed methods research is to (1) analyse research on the problems in music education management in Thailand in the past 5–10 years and (2) explore the current resources of music education in Thai institutions under the Office of The Basic Education Commission (OBEC). The study found that (1) the problems regarding music education in Thailand were lack of experts, lack of music curriculum, lack of musical instruments and proper classrooms, administration systems, lack of budget, lack of music-related activities and disagreement in the perceptions of school directors and teachers; and (2) under the OBEC, there were 30, 112 schools in total with 6, 781, 130 students in the 2018 academic year. As for music teachers, the majority, 68.9%, possess an educational background in music or music education. Overall, most of the schools of all sizes tend to lack Thai, Western and Thai folk musical instruments.